ANALYSIS OF MISCONCEPTIONS AMONG TENTH GRADE STUDENTS ON BASIC CHEMISTRY CONCEPTS USING A TWO-TIER MULTIPLE CHOICE INSTRUMENT - Putri Gita Driya; Rana Yuswandi; Hayuni Retno Widarti; Laksmi Purnajanti (Universitas Negeri Surabaya, 2026)
This study aimed to identify the level of misconceptions held by tenth-grade students on the topic of the Fundamental Laws of Chemistry using a summative two-tier multiple-choice instrument, as well as to determine which conceptual areas were most frequently misunderstood. A descriptive quantitative research design was employed, involving Grade X students from a public senior high school in Malang as the research subjects. The instrument consisted of 15 two-tier multiple-choice items with reasoning. Instrument validity was examined using corrected item–total correlation analysis, showing that 14 out of 15 items had correlation coefficients greater than 0.30, while reliability analysis using Cronbach’s alpha yielded a coefficient of 0.840, indicating high internal consistency. Students’ responses were analysed by categorising them into three levels: understanding (U), misconception (M), and lack of conceptual understanding (LU). The results revealed that students experienced misconceptions across several concepts related to the Fundamental Laws of Chemistry, with the highest percentage occurring in Avogadro’s Law. This study contributes to secondary high school chemistry learning by providing a valid and reliable diagnostic instrument for identifying students’ misconceptions in fundamental chemistry concepts. Overall, the average percentages of students who demonstrated understanding, misconceptions, and lack of understanding were 71%, 24%, and 5%, respectively.